Hygienemaßnahmen auf der Intensivstation = Hygiene and infection control measures in intensive care units - Mutters, Reinier; Mutters, Nico T. (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2016)
The prevention of infections is the purpose of hospital hygiene/infection control using control and preventive measures and strategies to achieve this. Especially in intensive care units with seriously ill patients. The continuous increase of multidrug-resistant organisms (MDRO) and as a consequence difficult to treat infections clearly shows the importance of prevention. Furthermore success and failure of hygienic/infection control activities is one of the few measurable quality and performance characteristics in the era of quality medicine and is therefore crucial for the evaluation of hospitals. Consequently it is recommended to meet the challenges and understand hygienic/infection control measures as vital and essential for the hospital. Central topics of present-day prevention are presented.
Gesehen am 18.09.2019